2020
DOI: 10.1007/s00330-020-07079-y
|View full text |Cite|
|
Sign up to set email alerts
|

Forensic age estimation in living adolescents with CT imaging of the clavicula—impact of low-dose scanning on readers’ confidence

Abstract: Objectives Computed tomography (CT) imaging of the clavicula displays the reference standard for forensic bone age diagnostics in adolescents and young adults. Consequently, highest efforts on radiation reduction are warranted. Therefore, the aim of this study was to investigate the feasibility of low-dose (LD) CT imaging of the clavicula for age estimation in living adolescents. Methods A total of 207 non-contrast chest CT of 144 patients born bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…Real femur images for each age category are separately distributed except for age [12][13][14][15] and [16][17][18][19] since bone growth becomes slower until it ceases altogether (Figure 5). Meanwhile, distributions of real phalange images for age [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] highly overlap due to its smaller growth. BAPGAN-generated images have similar distributions to the real ones.…”
Section: T-sne Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real femur images for each age category are separately distributed except for age [12][13][14][15] and [16][17][18][19] since bone growth becomes slower until it ceases altogether (Figure 5). Meanwhile, distributions of real phalange images for age [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] highly overlap due to its smaller growth. BAPGAN-generated images have similar distributions to the real ones.…”
Section: T-sne Resultsmentioning
confidence: 99%
“…Because skeletal maturity progresses through discrete stages, pediatric medicine has correlated children's chronological age with bone age to investigate endocrinology, genetic, and growth disorders; but, time-consuming manual bone age assessment methods [1,2] suffer from intra-and interobserver variability. In this context, Convolutional Neural Networks have shown great promise in age assessment on various modalities and body regions, including hand/pelvic X-ray [3,4], clavicula Computed Tomography [5], and hand Magnetic Resonance Imaging [6].…”
Section: Introductionmentioning
confidence: 99%
“…Changes of reformation techniques have been reported to influence image quality [13] and viewing images in axial and coronal reformations are considered gold standard for the evaluation of the medial clavicular epiphysis in forensic age estimation [20][21][22]. While many important studies in the field forensic clavicular imaging have examined patients with hands positioned at the body [12], studies with retrospective analysis of the clavicle, especially those that use thoracic CT examinations, evaluated multiplanar reformations in patients with hands positioned upwards [23]. Furthermore, volume rendering techniques have been discussed for the evaluation of the medial clavicular epiphysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…32 Alternate modalities such as low-dose CT, magnetic resonance imaging (MRI) and ultrasonography (USG) can be used to visualise MCE fusion for age estimation. Low-dose CT represents a significant improvement over standard-dose CT, as the radiation exposure of low-dose CT is a fifth of that of standard-dose CT. Gassenmaier et al 33 conducted a study on age estimation using low-dose CT in 2020, and they reported that while there is a significant difference between the image quality of the low-dose and standard-dose CT images, age can still be estimated with relative accuracy using low-dose CT. Low-dose CT thus has a distinctive advantage over conventional radiography in terms of sensitivity in identifying the stages of MCE fusion, and over standard-dose CT in terms of minimising ionisation radiation. Visualisation of indicators of skeletal maturity using low-dose CT could thus prove to be the new gold standard in the science of forensic age estimation.…”
Section: Discussionmentioning
confidence: 99%